Manipulating polymer decomposition to alter burn performance in aluminium/poly(vinylidene fluoride) filaments. Issue 6 (13th October 2020) - Strutton, Jared W; Knott, Matthew; Bencomo, Jose A; Iacono, Scott T; Mates, Joseph E; Alston, Jeffrey R; McCollum, Jena M
Abstract: Filaments composed of aluminium powder and poly(vinylidene fluoride) (PVDF) were produced by melt‐processing to investigate the effect of particle size and loading on decomposition behavior and burn performance. Thermal analysis revealed that nanoscale Al samples decompose PVDF in one step through interactions with the Al particle surface. Microscale samples presented with two distinct decomposition steps: (1) accelerated decomposition through interactions with the Al particle surface and (2) pyrolysis. This behavior occurs due to the drastic change in Al specific surface area. The burn test revealed that the filaments experience a maximum flame speed near the stoichiometric concentration for each fuel size. Although there are variations in decomposition and burn behavior between particle sizes, burn product analysis shows that all melt‐processed filaments result exclusively in AlF3 formation in open‐air burns. This behavior is unique to melt‐processed energetic composites and may provide more insight to binder–particle interactions and the effect on burn properties in energetic composites. © 2020 Society of Chemical Industry Abstract :